APPLICATION OF ASSURE MODEL BASED ON CHARACTER EDUCATION IN IMPROVING LEARNING OF INDONESIAN CIVILIZATION HISTORY TOPIC ON THE FIFTH GRADE STUDENTS OF SDN 1 KLAPASAWIT IN THE ACADEMIC YEAR OF 2014/2015. - Kasanah, Irma Fatehkatun (KALAM CENDEKIA PGSD KEBUMEN, 2018)
The objectives of this research are to describe the steps in applications the ASSURE models based on character education and improve learning of Indonesian civilization history topic in social science. This research was a collaborative classroom action research (CAR). This research was conducted in three cycles. Sources of data were obtained from researchers, observers, students, teachers, and document. The techniques of collecting the data were observation, interview, check list, and test of students' learning outcomes. The conclusion of this research is the applications ASSURE models based on character education carried out with the appropriate steps can improve history learning of Indonesian civilization theme in social science learning of the fifth grade students of SD Negeri 1 Klapasawit in the academic year of 2014/2015.